The ‘Ahok’ Case: Blasphemy, Majoritarian Politics and Minority Rights in Indonesia - Christy, Giovanni; Sabu, Wani; Wahyuwidayati, Tri; Wiranto, Emi (Faculty of Law, Universitas Pekalongan, 2024)
This paper explores the interplay between legal authority and religious influence in Indonesia, focusing on the highly publicized blasphemy trial of Basuki ‘Ahok’ Tjahaja Purnama, the former Governor of Jakarta. The study investigates two central points: first, although the trial was officially held to determine whether Ahok’s statements constituted blasphemy, the court proceedings largely centered on interpreting the Qur’an, shifting the case’s emphasis from blasphemy to religious definition. Second, the sentence handed down by the judges was not only more severe than what the prosecutors recommended but also indicative of deeper political dynamics. The paper contends that the verdict was influenced by majoritarian political forces, particularly in preserving Islamic dominance in a nation where Muslims form the majority, with Ahok representing a rare example of a Christian, Chinese-Indonesian holding high political office. Ultimately, the study argues that Indonesian courts frequently play an active role in reinforcing majoritarian narratives by legally defining religion, contributing to a broader regional trend where religious discourse is shaped by socio-political majoritarianism in Asian contexts.